Taxonomic revision and cladistic analysis of the species of Zethus mexicanus group (Linnaeus, 1758) sensu Bohart & Stange, 1965 (Hymenoptera, Vespidae, Eumeninae) - Golfetti, Ivan F. [UNESP]; Lopes, Rogerio B. [UNESP]; Noll, Fernando B. [UNESP] (Magnolia Press, 2020)
The Zethus mexicanus group sensu Bohart & Stange (1965) consists of four species in the subgenus Zethusculus: Zethus brasiliensis de Saussure, 1852, Z. mexicanus (Linnaeus, 1758) (both subdivided into three subspecies each), Z. magnus de Saussure, 1852 and Z. wal doi Zavattari, 1912. Color patterns and distribution have been used to differentiate the subspecies until now. However, these patterns may vary among individuals, and the distribution of specimens examined in this study showed overlap between subspecies. The analysis of external morphology did not show significant differences, making the subspecific division unnecessary. Thus, the following synonyms are proposed: Zethus brasiliensis fuscatus Boharth & Stange, 1965 n. syn. and Z. brasiliensis panamensis Boharth & Stange, 1965 n. syn. are junior synonyms of Z. brasiliensis brasiliensis; and Z. mexicanus erythrogena Boharth & Stange, 1965 n. syn. and Z. mexicanus lugubris Perry, 1833 n. syn. are junior synonyms of Zethus mexicanus mexicanus. Furthermore, the following status changed are proposed: Z. brasiliensis brasiliensis de Saussure, 1852 stat. rev. to Z. brasiliensis; and Z. mexicanus mexicanus (Linnaeus, 1758) stat. rev. to Z. mexicanus. In addition, a cladistic analysis, using terminals with representatives of the three subgenera of Zethus and one species of Ctenochilus, recovered the monophyly of the Zethus mexicanus group, as well as the subgenus Zethusculus, but rendered the arietis group paraphyletic. An identification key and redescriptions are given for the species in the group of Zethus mexicanus sensu Bohart & Stange (1965).
Keywords: Phylogeny; taxonomy; Zethini